- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,936

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,936

- Moderator
- #2

- Feb 7, 2012

- 2,799

Use Vieta's relations. The sum of the roots of the first equation is $4$, and the sum of the roots of the second equation is $-4$. So if the roots of the first equation are $\alpha,\ \beta$ and $\gamma$, then the roots of the second equation are $\alpha,\ \beta$ and $\gamma-8$. Vieta's relations tell us that

$$\alpha\beta + \beta\gamma + \gamma\alpha = 9/2,\qquad \alpha\beta + (\alpha+\beta)(\gamma-8) = -7/2.$$ Therefore $-\frac72 = \frac92 - 8(\alpha+\beta)$, from which $\alpha+\beta = 1$. But $\alpha + \beta + \gamma = 4$, and so $\gamma=3$ (and $\gamma-8 = -5$).

Putting $x=3$ as a solution to the first equation, you find that $p=-9$; and putting $x=-5$ as a solution to the second equation, you find that $q=15$.

You can then find $19q + 99p = -606$ but that seems a bit pointless.

- Jan 26, 2012

- 183

I thought the same but my way was a little longer. There must be a clever way at getting to the answer.

- Thread starter
- Admin
- #4

- Feb 14, 2012

- 3,936

Hmm...now that I see how

Hi

Let a, b, and m be the roots of the equation \(\displaystyle 2x^3-8x^2+9x+p=0\) and a, b and k be the roots of the equation \(\displaystyle 2x^3+8x^2-7x+q=0\).

We see that the sum of the roots for both equations are:

\(\displaystyle a+b+m=4\)

\(\displaystyle a+b+k=-4\)

Subtracting the second equation from the first equation, we obtain:

\(\displaystyle m-k=8\)

and the product of the roots for both equations are:

\(\displaystyle abm=-\frac{p}{2}\), \(\displaystyle abk=-\frac{q}{2}\)

Dividing these two equations, we obtain:

\(\displaystyle \frac{m}{k}=\frac{p}{q}\)

By Newton Identities, we have:

\(\displaystyle (a^2+b^2+m^2)(2)+(-8)(4)+2(9)=0\implies a^2+b^2+m^2=7\)

\(\displaystyle (a^2+b^2+k^2)(2)+(8)(-4)+2(-7)=0\implies a^2+b^2+k^2=23\)

Subtracting these two equations yields:

\(\displaystyle k^2-m^2=16\)

\(\displaystyle (k+m)(k-m)=16\)

\(\displaystyle (k+m)(-8)=16\)

\(\displaystyle m+k=-2\)

Solving the equations $m+k=-2$ and $m-k=8$ for both $m$ and $k$, we get $m=3$ and $k=-5$.

When $m=3$, \(\displaystyle a+b+3=4\implies a+b=1\)

Substituting $m=3,\,k=-5,\,a+b=1$ back into the equations \(\displaystyle a^2+b^2+m^2=7\), \(\displaystyle abm=-\frac{p}{2}\) and \(\displaystyle abk=-\frac{q}{2}\), we see that:

\(\displaystyle (a+b)^2-2ab+(3)^2=7\)

\(\displaystyle (1)^2-2ab+(3)^2=7\)

\(\displaystyle ab=\frac{3}{2}\)

Hence, \(\displaystyle \frac{3}{2}(3)=-\frac{p}{2}\implies p=-9\) and \(\displaystyle \frac{3}{2}(-5)=-\frac{q}{2}\implies q=15\).

And this gives \(\displaystyle 19q+99p=19(15)+99(-9)=-606\)

- Admin
- #5